Old Age-Related Stereotypes of Preschool Children - Flamion, Allison; Missotten, Pierre; Jennotte, Lucie; Hody, Noémie; Adam, Stéphane (Frontiers in Psychology, 2020)
Ageist attitudes have been discovered in children as early as 3 years. However, so far very few studies, especially during the last decade, have examined age-related stereotypes in preschool children. Available questionnaires adapted to this population are scarce. Our study was designed to probe old age-related views in 3- to 6-year-old children (n=126) using both an open-ended Image-of-Aging question and a new pilot tool, called Young Children’s Views of Older People (YCVOP), based on a visual analog scale illustrated by cartoons. Parental views of older people were also collected. The YCVOP was easy to use and internally consistent. Both that scale and the Image-of-Aging question showed globally favorable views of older people in preschool children, especially regarding warmth and smartness traits. However, assessment of physical capacity and independence tended to be negative. The overall results were in line with the low-competence, high-warmth stereotype of older people that is common in young adults and school-age children and was found in parents in the current study (Stereotype Content Model). Strikingly, children’s views did not correlate with those of their parents’: The children’s responses appeared more personal and emotional, while the parents tended to adopt global stereotypes. The preschoolers’ views of older people were much more positive in those who spontaneously evoked their grandparents when asked to think of an old person. In conclusion, this study, introducing a new visual tool to assess age-related stereotypes, suggests ambivalent views of older adults start in preschool children and are influenced by grandparents relationships.